The time-dependent motility and longevity of stallion spermatozoa diluted in different spermatozoal concentrations and extenders during cool-storage - Bozkurt, T.; Turk, G.; Gur, S. (Ecole Nationale Veterinaire Toulouse, 2007)
The aim of this study was to investigate the time-dependent changes in motility and longevity of stallion spermatozoa diluted in different spermatozeal concentrations and extenders during cool-storage at 5 degrees C. Ten purebred Arabian stallions, ranging from 10-24 years of age, were used. Three semen samples were collected from each stallion by artificial vagina. Each ejaculate of 10 stallions was diluted in 3 spermatozoal concentrations (25, 50, and 75x 10(6) in 1 ml of extender) in 3 different extenders (milk-, TRIS-based, and glucose-lactose). Sperm motility was determined at 0, 2, 4, 24, 48, 72, 96 and 120(th) h after the semen was diluted. All ejaculates of each Arabian stallion had a mean initial motility >= 80%. When it was compared the time-dependent effects of different spermatozoal concentrations in the same extender; the diluted semen with low (25x10(6)) spermatozoal concentration had greater motility and longevity than medium (50x10(6)) and high (75x10(6)) spermatozoal concentration for each extender at all times during examination period. Similarly, when it was compared the time-dependent effects of different extenders in the same spermatozoal concentration; spermatozoa diluted with milk-based extender had higher motility and longevity than TRIS-based and glucose-lactose extenders for each spermatozoal concentration at all times. In conclusion, the stallion semen must be mixed with an appropriate extender that helps to the protection of spermatozoa, and spermatozoal concentration in the extender should be low level in order to gain maximum benefit from cooled stallion semen. Among the tested extenders the milk based extender preserved motility for a longer time.
Keywords: spermatozoal concentration; extender; sperm motility; longevity; stallion